PRACTICALLY DIVIDED SEGMENT OF PROFESSIONAL PREPARATION OF STUDENTS IN HIGHER SCHOOL (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The article deals with the problem of practical training of students of the first (Bachelor's) and the second (Master's) higher education levels and ways to increase the effectiveness of the system of practical training of students in higher education. The results of the empirical study of the student's experience in passing the practice as an integral part of the process of training specialists in higher educational institutions in accordance with the standards of educational activity and higher education. The principles and tasks of the University's educational activities regarding practical training of students, types of practical training of students are considered. The ways of improving the practical training of students of higher educational establishments, the level of mastering practical skills, methods of mastering skills, the method of assessment (self- assessment) of mastering skills, are determined, as well as the criteria of students' practical training, the problems of practical training of students and the factors influencing level of student satisfaction with passing the practice.
Keywords: higher education, educational activity, practical training, practice, educational practice, educational and industrial practice, peda- gogical practice, assistant practice, research (undergraduate) practice, the effectiveness of passing the practice.